Mormon Visual Culture and the American West - Rees, Nathan, 1981- author.
1 online resource (166 pages
Keywords: This book explores the place of art in Latter-day Saint society during the first50 years of the Utah settlement, beginning in 1847. Nathan Rees uncovers the critical role that images played in nineteenth-century Mormon religion, politics, and social practice. These artists not only represented, but actively participated in debates about theology, politics, race, gender, and sexuality at a time when Latter-day Saints were grappling with evolving doctrine, conflict with Native Americans, and political turmoil resulting from their practice of polygamy. The book makes an important contribution to art history, Mormon studies, American studies, and religious studies.